(untitled) (Ozone Therapy Global Journal, 2016)
Objective: to evaluate the effect of ozone on the tissue surrounding implant retained mandibular overdenture both clinically and radiographically Material and Methods: Sixteen systematically healthy completely edentulous male patients ranged from 40-60 years were participating in this study to receive mandibular implant overdenture retained by two implants in the canine area. Eight patients for every group, group I: (control group) patients received two implants which following the conventional methods and group II: (test group) patients received two implants which following the conventional methods nevertheless; irrigation with ozonized water of 25µg/mL concentration was applied during the osteotomy procedure instead of saline. Ozone gas of 60 µg/mL concentration was applied topically in the performed osteotomy sites before the insertion of the implants. Clinical and radiographic evaluations were carried out for every patient at the time of loading with the prosthesis, then three, six and up to 12 months respectively. Results & conclusion: Ozone therapy accelerates and enhances the osseointegration of titanium implants; increases bone density in peri-implant interface and reduce the anticipated marginal bone loss.